2018
DOI: 10.1158/0008-5472.can-17-3205
|View full text |Cite|
|
Sign up to set email alerts
|

TNFRSF19 Inhibits TGFβ Signaling through Interaction with TGFβ Receptor Type I to Promote Tumorigenesis

Abstract: Genetic susceptibility underlies the pathogenesis of cancer. We and others have previously identified a novel susceptibility gene , which encodes an orphan member of the TNF receptor superfamily known to be associated with nasopharyngeal carcinoma (NPC) and lung cancer risk. Here, we show that TNFRSF19 is highly expressed in NPC and is required for cell proliferation and NPC development. However, unlike most of the TNF receptors, TNFRSF19 was not involved in NFκB activation or associated with TRAF proteins. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 47 publications
0
33
1
Order By: Relevance
“…Sequence analysis showed that the residues altered by the two mutations are conserved among the members of the TGF‐β receptor family, and thus may be functionally and evolutionarily important . Downregulation of TGF‐β signaling by miR‐93‐targeting TGFBR2 and by TNFRSF19 interaction with TGF‐β receptor I has been reported in NPC to counteract growth inhibition mediated by TGF‐β. In agreement with these previous findings, we showed that these two mutations in TGFBR2 also prevented the growth inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence analysis showed that the residues altered by the two mutations are conserved among the members of the TGF‐β receptor family, and thus may be functionally and evolutionarily important . Downregulation of TGF‐β signaling by miR‐93‐targeting TGFBR2 and by TNFRSF19 interaction with TGF‐β receptor I has been reported in NPC to counteract growth inhibition mediated by TGF‐β. In agreement with these previous findings, we showed that these two mutations in TGFBR2 also prevented the growth inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Photographs showed the appearance of tumor-bearing nude mice and representative tumor gross. Tumor volumes were measured at day 7,14,21,26,28,32,35,39,42,46, and 48 postinoculation, respectively. Data represented as the mean ± SEM (n = 6) and were analyzed by Student's t test.…”
Section: Discussionmentioning
confidence: 99%
“…We performed OLINK biomarker analysis for a panel of inflammation and cancer-related proteins. This analysis showed that several inflammation-associated factors [CD160 (23), CD27 (24), IL12B (25) and TNFRSF19 (26)] and cancer biomarkers [hK8 (27), Nectin4 (28), KLK13 (29) and CTSV (30)] were correlated with BMI only in breast cancersusceptible individuals, but not in healthy controls (Fig. 1C).…”
Section: Identification Of Plasma Factors From Breast Cancer-susceptimentioning
confidence: 91%
“…3-5). The only inflammation-related genes upregulated by plasminogen were Cxcl9 (an antiangiogenic and anti-fibrotic factor) 24 and Tnfrf19 (an inhibitor of TGF-β signaling) 25 .…”
Section: Plasminogen Treatment Of Radiation-induced Wounds Results Inmentioning
confidence: 99%